A one health approach to tackling AMR and why gender matters: findings from pastoralist communities in Tanzania - Barasa, Violet (Frontiers in Global Women's Health, 2024)
Introduction Inappropriate use of antimicrobials is a major driver of AMR in low-resource settings, where the regulation of supply for pharmaceuticals is limited. In pastoralist settings in Tanzania, men and women face varying degrees of exposure to antibiotics due to gender relations that shape access and use of antimicrobials. For example, critical limitations in healthcare systems in these settings, including inadequate coverage of health services put people at risk of AMR, as families routinely administer self-treatment at home with antimicrobials. However, approaches to understanding AMR drivers and risk distribution, including the One Health approach, have paid little attention to these gender considerations. Understanding differences in access and use of antimicrobials can inform interventions to reduce AMR risk in community settings. This paper focuses on the gendered risk of AMR through a study of gender and social determinants of access to and use of antimicrobials in low-resource pastoralist settings in Tanzania. Methods A mixed methods approach involving household surveys, interviews and ethnographic participant observation in homes and sites of healthcare provision was used, to investigate access and administration of antibiotics in 379 adults in Naiti, Monduli district in northern Tanzania. A purposive sampling technique was used to recruit study participants and all data was disaggregated by sex, age and gender. Results Gender and age are significantly associated with the use of antibiotics without a prescription in the study population. Young people aged 18-24 are more likely to use unprescribed antibiotics than older people and may be at a higher risk of AMR. Meanwhile, although more men purchase unprescribed antibiotics than women, the administration of these drugs is more common among women. This is because men control how women use drugs at the household level. Discussion AMR interventions must consider the critical importance of adopting and implementing a gender-sensitive One Health approach, as gender interacts with other social determinants of health to shape AMR risk through access to and use of antimicrobials, particularly in resource-limited pastoralist settings.